Excel Files for Teaching Two Dimensional Motions and their Curvature (Global Journal of Science Frontier Research, 2017)
Spreadsheets are presented which can help students to understand the the vector representation of velocity, acceleration and force, and the understanding of the radius of curvature. The examples include: sinusoidal curve, cardioid, Neile's parabola, motion of a charged body on which act a combination of magnetic and electric field, a body sliding on a rotating disk.
Keywords: Spreadsheets; body sliding; electric field; rotating disk